Production of settlements on the basis of a spiritual space :A Case Study of Parangtritis Settlements of Yogyakarta, Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Parangtritis, is a settlement existed on the coastal area of Yogyakarta. As an absolute space. ParangirilLs has its own characteristic as a cluster of vernacular settlements. The underpinning of the existence of Parangtritis is a belief of people that Parangritis is a place where the main, gate of the unseen kingdom of Queen of the South (the Southern Goddess) is located. With this underpinning of an abstract space, Parangtritis had transformed to a si3,irirual space, a cultural space, a social space, and recently to a commercial space. The Transformation of space is in line with Lefebvres concept of the production of space, Which works under the a system of Interconnected-relutions (engagement). This paper aims to present some evidencas, conceptual findings, and theoretical discussions where an engagement of absolute space and abstract space occurs in the case Parang,tritis settlements of Yogyakarta of Indonesia. key words: Parangtritis, Spiritual Space, social space, interconected space